Thermodynamic analysis of the schemecycle design of a heatingcoolingmachinefor an individual house - Morozyuk, Larisa; Sokolovska-Yefymenko, Viktoriia; Kandieieva, Vera; Moshkatiuk, Andrii; Kukoliev, Artem (Eastern-European Journal of Enterprise Technologies, 2019)
The direction of the research is the thermodynamic analysis of the scheme-cycle designof a heating and cooling machine for an individual house powered by autonomous solar photovoltaic system of providing private consumers with the year-roundheating and cooling in conditions of dry tropical climate. For the analysis, a single-stage compressor refrigerating machine was used, which operates in two modes: refrigeration forair conditioning and heat pump for heating, covering all rooms in the house. Change of the modes is made seasonally or during the day depending on the ambient temperature. The energy efficiency of the refrigerationcycle(“energy” problem) associated with the properties of the working fluid, and cycle size(“transport”problem) associated with the scheme-cycle design, equipment mass and investment costs,were determined. The study used the working fluids R404a, R134a, R410, R290, R600a, R32, which are neither prohibited nor expired. Calculations were performed separately for each mode. The results showed that the R290, R600a working fluids have a high efficiency in both modes, R404A, R410, R32 have the same energy efficiency, differing by no more than 10%, R134a is incompetitivein the heating mode. Among the cyclesizes, R32, R410 have the advantagewith the valueshalf the size of R290, R404A, R600a and R134a are not included in the alternative group. Based on the thermodynamic analysis and monitoring of the market of working fluids, only R32 can be recommended for real projects. A separate thermodynamic analysis of thescheme-cycle designs for CO2 – the real prospect of refrigeration equipmentwas carried out.